Tetrandrine Modulates Rheb-mTOR Signaling-Mediated Selective Autophagy and Protects Pulmonary Fibrosis - Liu, Yuanyuan; Zhong, Wenshan; Zhang, Jinming; Chen, Weimou; lu, Ye; Qiao, Yujie; Zeng, Zhaojin; Huang, Haohua; Cai, Shaoxi; Dong, Hangming (Frontiers in Pharmacology, 2021)
Idiopathic pulmonary fibrosis is a progressive fatal disease characterized by interstitial remodeling, with high lethality and a lack of effective medical therapies. Tetrandrine has been proposed to present anti-fibrotic effects, but the efficacy and mechanisms have not been systematically evaluated. We sought to study the potential therapeutic effects and mechanisms of tetrandrine against lung fibrosis. The anti-fibrotic effects of tetrandrine were evaluated in bleomycin-induced mouse models and TGF-β1-stimulated murine lung fibroblasts. We performed Chromatin Immunoprecipitation (ChIP), Immunoprecipitation (IP) and mRFP-GFP-MAP1LC3B adenovirus construct to investigate the novel mechanisms of tetrandrine-induced autophagy. Tetrandrine decreased TGF-β1-induced expression of α-smooth muscle actin, fibronectin, vimentin and type 1 collagen and proliferation in fibroblasts. Tetrandrine restored TGF-β1-induced impaired autophagy flux, accompanied by enhanced interaction of SQSTM1 and MAP1LC3-Ⅱ. ChIP studies revealed that tetrandrine induced autophagy via increasing binding of NRF2 andSQSTM1 promoter. Furthermore, tetrandrine inhibited TGF-β1-induced phosphorylation of mTOR by reducing activation of Rheb. In vivo tetrandrine suppressed the bleomycin-induced expression of fibrotic markers and improved pulmonary function. Our data suggest that protective effect of tetrandrine against lung fibrosis might be through promoting Rheb-mTOR and NRF2-SQSTM1 mediated autophagy. Tetrandrine may thus be potentially employed as a novel therapeutic medicine against IPF.